Does Libertarianism Provide a Justification for Vaccine Hesitancy?. Issue 2 (29th April 2022) - Butler, Jethro; Sorell, Tom
Abstract: Libertarian ideas of self‐ownership and the priority of bodily autonomy have featured prominently in the political debate over vaccination programmes and the justifiability or otherwise of restricting the liberty of the unvaccinated. In this article we look at a selection of recent right‐libertarian literature to show that there is a considerable divergence between the application of consistent libertarian principles to this issue by academic libertarians and the strident opposition to vaccination programmes and vaccine mandates expressed by people who profess to be libertarians in the public‐political debate.